Direct Torque Control Of Induction Machine Using 3-Level Neutral Point Clamped Inverter - Huzainirah, Ismail; Fazlli, Patkar; Auzani, Jidin; Sundram, Ramahlingam; Muhd Khairi, Abd Rahim; Yusnida, Ahmad Tarmizi; Atikah, Razi (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
This paper presents a Direct Torque Control (DTC) of induction motor drives utilizing 3-level neutral-point clamped (NPC) multilevel inverter. This research aims to provide a simple strategy to address capacitor voltage balancing problem of NPC inverter as well as produce better performance for DTC of induction motor in term of reducing torque ripple and high switching frequency. The proposed method uses 2-level hysteresis comparator to restrict the error of upper and lower capacitor voltages and then generate a signal which determine either to increase or decrease the particular capacitor voltage. Using that information, the appropriate selection of small voltage vectors is tabulated in look-up table (LUT) to stabilize the mismatched of capacitor voltage. Simulation results are presented to show the effectiveness of the proposed capacitor voltage balancing strategy.